The Implementation of Sekaya Maritim in Muara Village Fishermen Village, Wanasalam District, Lebak Regency, 2000-2018 - Trivia, Melly Dwi; Indriyanto, Indriyanto (Diponegoro University, 2024)
This article focused on the development of the Fishermen's Village area in Muara Village, Wanasalam District, Lebak Regency during the implementation of the Sekaya Maritim Program from 2000 to 2018. “Sekaya Maritim” stands for Seribu Kampung Nelayan yang Mandiri, Tangguh, Indah dan Maju. The program is part of the process and efforts to make fishermen more independent so that they can improve their living standards. The Sekaya Maritim program is implemented in almost all coastal areas of Indonesia, especially fisheries centers. Therefore, Muara Village as one of the villages in Lebak Regency became one of the locations for the implementation of Sekaya Maritim. The condition of the community and infrastructure in Muara Village Fishermen Village still needs attention. This is because the level of community welfare is still low and the condition of the infrastructure also looks alarming. Through the historical method, the results show that the implementation of Sekaya Maritim in Muara Village was carried out by providing various assistance and infrastructure development. The various changes that occurred as a result of the Sekaya Maritim Program have at least improved community welfare due to the opening of various accesses for the community and adequate facilities.